(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This scientific article contains theories of scientists about the psychological mechanisms of personality, factors motivating the use of individual defense mechanisms, and the reasons for their occurrence.